Analysis of right and left ventricular deformation in former world class swimmers: evaluation using speckle tracking - Knackstedt, C.; Hildebrandt, U.; Schmidt, K.; Syrocki, L.; Lang, A.; Bjarnason-Wehrens, B.; Schummers, G.; Stapf, D.; Becker, M.; Predel, H. G. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: There is a longstanding debate over the long-term effect of intensive endurance training on cardiac function. Usually, echocardiography has been used as a global evaluation of left ventricular (LV) or right ventricular (RV) function and dimensions. Recently, speckle tracking strain (ST) has provided an analysis of regional RV and LV function. Thus, the intention of the study was to carefully evaluate cardiac function in a group of former world class swimmers applying longitudinal strain (LS) and circumferential strain (CS) analysis.